IL-21 Is Associated With Virological Relapse of HBeAg Positive Chronic Hepatitis B After Discontinuance of Entecavir - Huang, Lihua; Zhou, Li; Gan, Jianhe; Yang, Wenlong; Dai, Yaping; Su, Tingting; Qiu, Yuanwang (Turkish Journal of Gastroenterology, 2021)
Background: To investigate the association between interleukin-21 (IL-21) expression level and virological relapse (VR) of HBeAg positive chronic hepatitis B (CHB) after discontinuance of entecavir (ETV).Methods: The serum IL-21 level of 112 CHB patients was measured at 0, 12, 24, 52, and 104 weeks after ETV discontinuance. ELISA was used for the measurement of serum IL-21 level. VR was defined as two continuous examinations with an interval of 1 month with both showing HBV DNA >10 000 copies/mL after drug discontinuance.Results: The serum IL-21 levels at 0, 12, 24, 52, and 104 weeks after discontinuance of ETV were significantly higher in the durable virological remission (DVR) group than in the VR group (all P < .01). The area under the ROC curve (AUC) was 0.728 (95% CI: 0.630-0.827, P < .001), while the best cut-off value was 49.8 pg/mL. Multivariate Cox model showed that the factors affecting the relapse included age, followed by HBsAg level at the serological conversion of HBeAg and serum IL-21 level (all P < .05).Conclusion: Serum IL-21 level at ETV discontinuance is an independent risk factor for CHB relapse. IL-21 acts as an immunomodulatory factor in maintaining DVR in HBeAg positive CHB patients after ETV discontinuance.